Learning Local Content Based On The Excellence Of Shell Shells And Growing The Entrepreneurship Soul In Elementary School - Andi Imrah Dewi; Akina Akina (Journal on Education, 2021)
This research leads to research on the development of local content models based on the advantages of clam shells in growing entrepreneurship. Art education is certainly interpreted comprehensively and contextually, art learning is not only viewed contextually and philosophically, but also becomes practical art learning, so as to be able to develop intelligence effectively. intellectual, emotional intelligence and spiritual intelligence, various approaches to art learning can be utilized according to the psychological level of students and school conditions such as the free expression approach, the discipline approach and the multicultural approach as well as the thematic approach, from these various approaches, of course, teachers have a very important role. Such as developing strategies and methods used, including in the process of assessing and evaluating student learning. So that everything needs to be prepared in the unit of learning and teaching tools. Art is a conscious effort to pass down all forms of transformation both in the fields of culture and art education which is a necessity where culture gives birth to art. The meaning of art education is the provision of aesthetic experiences, both in the form of experiencing the value of aesthetic beauty, which means that there are two parts, the first is appreciating and the second is creation. Creating learning models to develop students' aesthetic experiences so that they have sensitivity, creativity, initiative and taste in the value of expression and concern for the natural environment and social culture that exist around them Knowing how much influence the learning model has to foster an entrepreneurial spirit from a creativity that is done by students by doing various uses of used materials, waste, or processed products that can produce a craft that can be used 3) Knowing the effectiveness of the learning development model for arts, culture and crafts produces something beautiful and can be useful of course through the process the creativity and skills possessed by students in gaining experience in learning The research model used, namely the Research and Development (R&D) model, is a research method used to research so as to produce new products, and then test the effectiveness of these products. a learning model guide that becomes a reference for teachers of arts and crafts education in art learning for high school elementary school students.